2020
DOI: 10.1002/psp4.12485
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Time‐to‐Event Model for Acute Exacerbations in Idiopathic Pulmonary Fibrosis

Abstract: We describe a parametric time‐to‐event model for idiopathic pulmonary fibrosis (IPF) exacerbations and identify predictors of exacerbation risk using data obtained for the tyrosine‐kinase inhibitor nintedanib in two phase III studies (INPULSIS‐1/2). Parametric survival analysis was performed on time to first exacerbation (censoring on day 372), with univariate analysis to select statistically significant covariates (P = 0.05). Multivariate covariate models were developed using stepwise covariate modeling with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…A TTE analysis has been published for time-to-first exacerbation in idiopathic pulmonary fibrosis. 32 The model we present can be used to predict asthma exacerbations based on observed time-varying covariates from other patient studies (even for other drugs) where the relevant time-varying covariates have been collected, but the patient material and study duration is not necessarily sufficient for directly assessing outcomes in exacerbations. This information would be relevant during early stage asthma drug development and can likely streamline decision making regarding design for future studies within asthma drug development (e.g., dose selection and sample size determinations).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A TTE analysis has been published for time-to-first exacerbation in idiopathic pulmonary fibrosis. 32 The model we present can be used to predict asthma exacerbations based on observed time-varying covariates from other patient studies (even for other drugs) where the relevant time-varying covariates have been collected, but the patient material and study duration is not necessarily sufficient for directly assessing outcomes in exacerbations. This information would be relevant during early stage asthma drug development and can likely streamline decision making regarding design for future studies within asthma drug development (e.g., dose selection and sample size determinations).…”
Section: Discussionmentioning
confidence: 99%
“…Models for predicting exacerbations in chronic obstructive pulmonary disease exist 30,31 (these are not parametric TTE models). A TTE analysis has been published for time‐to‐first exacerbation in idiopathic pulmonary fibrosis 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All models 15 , 16 , 28–45 were at high ROB in development or validation. Eight models 16 , 35–37 , 39 , 40 , 42 , 45 are rated as high ROB in applicability. Figures 2 and 3 show the proportion assessment for each PROBAST item and proportion of studies with potential bias using PROBAST, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This is most commonly due to concerns about applicability in domain 1 (population) for included randomized clinical trials or specific groups. In addition, two 37 , 40 out of 20 studies’ outcomes included exacerbation, but the definition of acute exacerbation may have varied between studies and may have been expanded to include events for which a trigger can be identified, such as infection. 46 …”
Section: Resultsmentioning
confidence: 99%